INFLUENCE OF TEMPERATURE ON THE PERFORMANCE OF A COMMERCIAL SOLAR BATTERY USED IN NIAMEY, NIGER - Abourahamane, Saidou Boulhassane1; Abdoul Razak 1, Boukari Oussoumane; Abdoulkadri, Ayouba Mahamane*; Moutari, Souley Kallo2; Hassane, Adamou Hassane; Rabani, Adamou1 (university of eloued جامعة الوادي, 2023)
This work aimed to assess the influence of temperature on the performance parameters of a commercial solar battery used in the city of Niamey in Niger. After an investigation, a sealed lead acid battery (VRLA-AGM, 12 V-80 Ah) was subjected to various tests. Based on the meteorological data of one year from the city of Niamey, experiments were carried out at different temperatures (17 °C, 30 °C and 42 °C). The experimental results showed that the battery capacity, discharge time, charge time and gassing rate are relatively large at high temperature (42 °C). However, the battery internal resistance is relatively high at low temperature (17 °C). Relatively better performance was obtained at the temperature of 30 °C.
artikal
Keywords: Lead-acid solar battery, inventory, temperature, performance, Niamey.